Observation of a Relationship Between Orbital-Specific Molecular Similarity Index and Toxicity of Methylcarbamate Derivatives - Sihan Long; Yuuki Onitsuka; Soichiro Nagao; Masahiko Takahashi (Molecules)
We report a computational investigation on the reachability of the molecular similarity index (MSI) approach for predicting the relative drug strength of methylcarbamate derivatives. Traditional MSI values have been obtained by calculating the overlap integral of total electron momentum densities between one molecule and another. Furthermore, we have proposed and tested orbital-specific MSI (OS-MSI) values, obtained by doing the same but with electron momentum densities of a selected molecular orbital (MO) such as the highest occupied MO (HOMO) and the lowest unoccupied MO (LUMO). In the calculations, a Boltzmann-weighted electron momentum density estimated by a theoretical probability distribution of rotamers was used, while the solvation effect was considered using the polarizable continuum model. It is shown that the traditional MSI values as well as the OS-MSI values for the HOMO do not have any correlation with experimental relative toxicity of the methylcarbamate derivatives. In contrast, it has been observed and found that the OS-MSI values for the LUMO exhibit a noticeable correlation with the experimental data. The reason behind this observation is discussed in relation to the drug reaction mechanism of the methylcarbamate derivatives.